First record of Scuttle fly, Megaselia (M) scalaris (Loew) (Diptera: Phoridae) as a parasitoid of Sunn pest, Eurygaster integriceps Puton (Hemiptera: Scutelleridae) from Iran - Laleh Ebrahimi; R. Henry L. Disney; Alireza Haghshenas; Ebrahim Gilasian; Masood Amir-Maafi; Shahram Shahrokhi Khaneghah (Egyptian Journal of Biological Pest Control, 2023)
Abstract The Scuttle fly, Eurygaster integriceps Puton (Hemiptera: Scutelleridae) is a key pest of wheat and barley. The pest is univoltine and migrates from wheat fields following harvest to high elevations; then, the following spring it moves back to the fields. Natural enemies may have an important role in decreasing the population’s level in overwintering sites. In the present study, adults of E. integriceps were collected from overwintering sites in Isfahan province, Iran, in October 2022 and transferred to the laboratory. One week after sampling, dead adults were isolated and divided into three groups: one group was dissected under a stereomicroscope, and parasitoid larvae were extracted from the cadavers; the second one was incubated in Petri dishes sealed with parafilm, individually for four weeks, and emerged pupae were collected; and the third group was incubated in the closed boxes, and emerged flies were collected for fixing and identification. Assessment of dissected adult E. integriceps under a stereomicroscope revealed that the insect was parasitized with Megaselia scalaris (Loew) (Diptera: Phoridae) larvae. Per adult, up to 13 larvae were found inside E. integriceps. The last instar larvae were pupated outside the E. integriceps body. This study is a new record of M. scalaris as a parasitoid of E. intergriceps in Iran.